2023
DOI: 10.3390/cells12050707
|View full text |Cite
|
Sign up to set email alerts
|

Hypotheses on Atherogenesis Triggering: Does the Infectious Nature of Atherosclerosis Development Have a Substruction?

Abstract: Since the end of the 20th century, it has been clear that atherosclerosis is an inflammatory disease. However, the main triggering mechanism of the inflammatory process in the vascular walls is still unclear. To date, many different hypotheses have been put forward to explain the causes of atherogenesis, and all of them are supported by strong evidence. Among the main causes of atherosclerosis, which underlies these hypotheses, the following can be mentioned: lipoprotein modification, oxidative transformation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…These diseases are linked to chronic infection in humans, as research has shown that these gatherings of biofilms release many virulence factors including toxins and proteases (13,14) thus damaging host tissues. Biofilm infection also poses additional risks to the host due to its low exposure to antibiotics and its ability to compete with the host for oxygen and nutrients (15,16). One of the most important activities of biofilms is the response Dispersion which releases bacteria from within the biofilm by decomposition of the biofilm matrix (17).…”
Section: Discussionmentioning
confidence: 99%
“…These diseases are linked to chronic infection in humans, as research has shown that these gatherings of biofilms release many virulence factors including toxins and proteases (13,14) thus damaging host tissues. Biofilm infection also poses additional risks to the host due to its low exposure to antibiotics and its ability to compete with the host for oxygen and nutrients (15,16). One of the most important activities of biofilms is the response Dispersion which releases bacteria from within the biofilm by decomposition of the biofilm matrix (17).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of these substances results in a complex pathophysiology with various cellular interactions and modulations involved that can result in vascular occlusion and/or plaque rupture or erosion that clinically manifests as myocardial infarction and stroke 3 . Importantly, there is accumulating evidence supporting a high degree of diversity of mechanisms underlying atherosclerotic disease and related thrombotic events 4,5 . Recent single-cell sequencing studies have revealed cellular resolution insights into atherosclerotic tissue in mice and humans, shedding light on cellular heterogeneity, cellular plasticity, and the contribution of different cell types to atherogenesis 6 .…”
Section: Mainmentioning
confidence: 99%